2017
DOI: 10.1111/jfb.13307
|View full text |Cite
|
Sign up to set email alerts
|

Museum samples could help to reconstruct the original distribution of Salmo trutta complex in Italy

Abstract: Partial D-loop sequences of museum specimens of brown trout and marble trout (Salmo trutta species complex) collected from Mediterranean rivers in the late 19th century were analysed to help to describe the native distribution of these species. All the individuals studied carried native haplotypes, the geographic distribution of which is consistent with published data. These results indicate that museum specimens from the 19th century could represent an opportunity to get a picture of the original genetic dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 24 publications
5
35
1
Order By: Relevance
“…Similar findings were recently obtained by Fabiani et al (2017) for the "macrostigma" Latium population, harbouring indeed AD and ME haplotypes. As for S. carpio, a single specimen belonged to AD lineage, thus confirming that this lacustrine trout does not represent a peculiar evolutionary line, but probably no more than an ecotype of the lake Garda (Splendiani et al 2017).…”
Section: Geographic Rangesupporting
confidence: 56%
See 2 more Smart Citations
“…Similar findings were recently obtained by Fabiani et al (2017) for the "macrostigma" Latium population, harbouring indeed AD and ME haplotypes. As for S. carpio, a single specimen belonged to AD lineage, thus confirming that this lacustrine trout does not represent a peculiar evolutionary line, but probably no more than an ecotype of the lake Garda (Splendiani et al 2017).…”
Section: Geographic Rangesupporting
confidence: 56%
“…Another significant study examined the possibility to use ancient DNA (aDNA) to disentangle the phylogeography of Italian trout (Splendiani et al 2017). In this paper, a partial sequence of D-loop was obtained from a trout collection deposited at the Zoological Museum "La Specola" of the Florence University.…”
Section: Geographic Rangementioning
confidence: 99%
See 1 more Smart Citation
“…For this reason our Me25, mainly characterized by SCR Mediterranean brown trout population, corresponds to 6 different haplotypes (Supplementary material, Table SI), including the one (MEcs1) that is considered basic of this lineages. This haplotype was distributed in Corsica, northern and central Italy in late nineteen century, before common stocking with Atlantic strains (Splendiani et al 2017) and was already present in prehistoric times in southern Italy (Splendiani et al 2016a). The same problem of sequence length is present for AD lineages; certainly the most common haplotype of this lineage AD-cs1, originally spread across Italian peninsula and Sardinia (Splendiani et al 2016a(Splendiani et al , 2017 is not present in our sampling area.…”
Section: Discussionmentioning
confidence: 76%
“…There is no current consensus about the validity of S. cetti (sensu Kottelat & Freyhof, 2007) as a species (or even as a distinct taxon within the S. trutta complex) and some authors prefer to simply include it into a more comprehensive "Mediterranean" S. trutta (e.g. Berrebi, 2015;Splendiani et al, 2017). Gratton et al (2014) analysed a diverse set of mitochondrial and nuclear markers and identified two main native genetic lineages in samples of Italian trouts: a widespread "peninsular" lineage, including samples of Salmo cenerinus, S. cettii and S. fibreni (all sensu Kottelat & Freyhof, 2007) and most of the genetic ancestry of the Garda Lake endemic Salmo carpio, and a "marble" lineage, represented by S. marmoratus populations.…”
mentioning
confidence: 99%